2003
DOI: 10.1074/jbc.m305357200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Charged Residues in Coupling Ligand Binding and Channel Activation in the Extracellular Domain of the Glycine Receptor

Abstract: The glycine receptor is a member of the ligand-gated ion channel receptor superfamily that mediates fast synaptic transmission in the brainstem and spinal cord. Following ligand binding, the receptor undergoes a conformational change that is conveyed to the transmembrane regions of the receptor resulting in the opening of the channel pore. Using the acetylcholine-binding protein structure as a template, we modeled the extracellular domain of the glycine receptor ␣1-subunit and identified the location of charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
83
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 23 publications
11
83
0
Order By: Relevance
“…from R271C to K276C) resulted in irreversible changes in the glycine EC 50 values without affecting the saturating current magnitudes (14,17). The same study also showed that the MTSET reaction rate of all these cysteines was relatively slow in the resting closed state but was increased dramatically in the glycine-bound state.…”
Section: Characterization Of Cysteine-substituted Mutant Glyrs-itsupporting
confidence: 55%
See 1 more Smart Citation
“…from R271C to K276C) resulted in irreversible changes in the glycine EC 50 values without affecting the saturating current magnitudes (14,17). The same study also showed that the MTSET reaction rate of all these cysteines was relatively slow in the resting closed state but was increased dramatically in the glycine-bound state.…”
Section: Characterization Of Cysteine-substituted Mutant Glyrs-itsupporting
confidence: 55%
“…A structural study of the Torpedo nAChR has shown recently (4) that these residues form an extramembranous extension to the M2 ␣-helix. This domain is likely to interact closely with loops 2 and 5 of the ligand-binding domain (4,17,18,23,24). A particular advantage of investigating this domain is that it lies outside the ligand-binding pocket (6), so changes in methanethiosulfonate reaction rates are unlikely to be influenced by steric effects of ligand binding.…”
mentioning
confidence: 99%
“…This model was first suggested by hydrophobicity plots of the ligand-gated channels and was recently confirmed by biochemical and crystallographic data from studies with nAChR (2, 28,29,32). Coincidentally, several recent studies showed similar channel gating mechanisms for the LGIC members; involving the ligand-binding domain and the extracellular loop between TM2 and TM3 (32)(33)(34).…”
Section: Discussionmentioning
confidence: 67%
“…We propose that the transition to the desensitized conformation is accompanied by an outward movement of the M2-M3 linker disengaging from the intrasubunit interactions with the ␤1-␤2 and ␤6-␤7 loops to establish intersubunit contacts with the pre-M1 region of the adjacent subunit. Studies in GlyR have shown that the substituted Cys in the M2-M3 linker is more water exposed in the open state than when the channel is in the closed conformation (20). The outward movement of M2-M3 also releases the ␤6-␤7 linker to now move downward into the intrasubunit cavity, interacting with tightly associated membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
“…15-17 and references therein), and it is known that this region contributes to both the lifetime of the open state and the kinetics of desensitization (18). The interface also contains several charged residues, and gating models have been proposed on the basis of the interactions between specific charged pairs (19,20). However, it is to be noted that these interactions are not conserved across the family (21).…”
mentioning
confidence: 99%